Continuum-orientation phenomena in ionization by positron impact - Fiol, Juan (2011)
Ionization collisions by positron impact at low and intermediate energies are investigated by means of a classical trajectory Monte Carlo (CTMC) simulation. Calculations of fully differential cross sections unveil a remarkable dynamical orientation of the electron–positron continuum dipole. Actually, by means of the CTMC simulation we show that, for electron velocities close to the final positron velocity, the dipole is narrowly oriented along the direction of motion of its centre-of-mass, with the negative charge pointing towards the residual target, i.e. emitted at lower energies than the positron. The characteristic features of this phenomenon are studied. Also, several future experiments and calculations are proposed. The possible outcomes of this further research might help to unveil the mechanisms responsible for the appearance of this orientation effect.